147, 146Sm–143, 142Nd, 176Lu–176Hf, and 87Rb–87Sr systematics in the angrites: Implications for chronology and processes on the angrite parent body. (15th December 2015) - Sanborn, Matthew E.; Carlson, Richard W.; Wadhwa, Meenakshi
Abstract: Angrites are a group of basaltic achondrites with distinctive mineralogic and geochemical characteristics that have the potential to provide insights into processes occurring on planetesimals in the early Solar System. These achondrites have been used as anchors linking the relative age information obtained from short-lived, extinct chronometers (e.g., Al–Mg, Hf–W, and Mn–Cr) with absolute chronometers (e.g., U–Pb). Angrites provide excellent examples of early differentiation processes, such as core formation and silicate differentiation, on protoplanetary bodies. The significant increase in the number of known angrite samples in recent years has offered the opportunity to compare several short- and long-lived isotopic systems in samples with different petrogenetic histories that formed on the same parent body. To this end, the 147 Sm– 143 Nd, 146 Sm– 142 Nd, 176 Lu– 176 Hf, and 87 Rb– 87 Sr isotope systematics have been investigated in a suite of plutonic, coarse-grained (NWA 4590, NWA 4801, and NWA 2999) and quenched, fine-grained (D'Orbigny) angrites. The coupled 147, 146 Sm– 143, 142 Nd systematics indicate possible isotopic disturbances in two angrites (D'Orbigny and NWA 2999) resulting from post-crystallization processes. The internal 146 Sm– 142 Nd isochrons of two coarse-grained angrites (NWA 4590 and NWA 4801) provide an updated best estimate of the initial Solar System 146 Sm/ 144 Sm ratio (i.e., at 4568 Ma) of 0.0084 ± 0.0003. The 176 Lu– 176 Hf isotope systematics in these angrites do not provide evidence of a previously proposed intense irradiation event in the early Solar System. The internal 176 Lu– 176 Hf isochrons for the NWA 4590 and D'Orbigny angrites provide an estimate for the Solar System initial 176 Hf/ 177 Hf ratio of 0.279775 ± 0.000031 (2 σ ) that agrees within uncertainty with the value of average chondrites reported by Bouvier et al. (2008). Finally, the calculated initial 87 Sr/ 86 Sr ratios based on the measured Sr-isotopic composition of plagioclase in these angrites yield an estimated initial 87 Sr/ 86 Sr ratio of 0.698980 ± 0.000011 for the angrite parent body. This is indistinguishable from a recently determined value for the Solar System initial 87 Sr/ 86 Sr based on values measured in calcium–aluminum-rich inclusions (CAIs) after correcting for nucleosynthetic effects in the CAIs. The low initial 87 Sr/ 86 Sr of the angrite parent body implies that it acquired its volatile element depleted characteristic within 1.8 Ma of Solar System formation, likely because it accreted from volatile depleted planetesimals that formed in the hot inner nebula. These integrated isotopic systematics suggest a complex history for the angrite parent body not previously inferred from short-lived chronometers and provide new estimates for the initial isotopic composition of the early Solar System.